Determinants to influence the credit risk of global Islamic Banks: application of static models - Shahari, Farihana; Rahman, Md. Saifur (The Empirical Economics Letters, 2018)
This paper aims to identify the determinants that influence the credit risk of global Islamic banks. The paper employs the static panel models in the investigation process and uses the multiple variables - focus variable, bank-specific variable and macroeconomic variables which are collected from the database of banks’ annual reports, DataStream and World Bank over the period from 2005 to 2012. The finding indicates that financial development index and profitability are key determinants to influence the credit risk of Islamic banks. The paper proposes significant policy implication for the Islamic bank to sustain in the competitive banking industry.